Digital Competence of Science Teachers at Jayapura City of Papua - Nurbaya Nurbaya; Hanida Listiani; Suriyah Satar; Maik Akobiarek (Postgraduate, University of Mataram, 2024)
The digital competence of science teachers is of vital significant to improving the quality teaching-learning process. The aim of this study is to know the level of digital competence of science teachers in Jayapura City. The methodology used was non-experimental and descriptive quantitative, with survey design. In such a context, 41 science teachers took part in this research, who were teaching in state junior high schools and private junior high schools. As for data collection tools, the study used 31-items of digital competence questionnaire, developed from 5 main areas of DigComp Framework (information and data literacy, communication and collaboration, digital content creation, safety, and problem solving). Based on data analyses, the digital competence of science teachers stood from high to very high level. Although the third and the fourth showed some indicator with the low ability in teachers’ competence.